Bentuk Tindak Tutur Perlokusi Ekspresif pada Dialog Tokoh Ian dalam Film Perayaan Mati Rasa Karya Umah Shahab - Farrel Rizki Saputra; Dyah Wijayawati; Bivit Anggoro Prasetyo Nugroho (Universitas Nahdlatul Wathan Mataram, 2026)
This study aims to describe the form of expressive perlocutionary speech acts in the dialogue of the character Ian in the film Perayaan Mati Rasa by Umay Shahab. This study is a qualitative descriptive study based on pragmatic studies, focusing on the use of language in the context of speech interactions. The research data are in the form of dialogue utterances of the character Ian containing expressive perlocutionary speech acts. The data were obtained through the Free Listening and Speaking (SBLC) method, which is a data collection technique by listening to the use of language without the researcher's direct involvement in the speech event, which is followed by a note-taking technique to systematically document the data. The collected data were then analyzed using the pragmatic equivalent method with the Determining Elements Selection (PUP) technique, namely analyzing speech based on the context of the speech situation and the determinants of meaning outside of language, such as the relationship between the speaker and the speech partner and situational conditions. Furthermore, the data were classified based on the theory of expressive speech acts proposed by Searle (1979), which includes forms of thanking, congratulating, apologizing, blaming, praising, expressing condolences, and complaining. The results of the study indicate that of the seven forms of expressive perlocutionary speech acts, six were found: thanking, apologizing, blaming, praising, expressing condolences, and complaining. Congratulating was not found. The most dominant form of expressive perlocutionary speech act was complaining, which represents the emotional distress and inner conflict experienced by the main character. This research is expected to contribute to the development of pragmatic studies, particularly the analysis of expressive perlocutionary speech acts in film media, as well as provide implications for the field of language and literature education as teaching materials for discourse analysis and learning to appreciate audiovisual literary works.